Development of QuizWhizzer Learning Media for Elementary Schools - feri hermawan; Diyas Age Larasati; Savitri Suryandari (Universitas Negeri Semarang, 2026)
This study aimed to develop QuizWhizzer media on the topic of currency values and their functions and to determine its validity and effectiveness in elementary school IPAS learning. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research was conducted at SDN Pakis V Surabaya involving media experts, material experts, a third-grade teacher, and 24 third-grade students. Data were collected through observation, interviews, questionnaires, and tests. Data were analyzed using percentage techniques to determine the validity and practicality of the media, while learning improvement was analyzed using the N-Gain test assisted by SPSS version 31.0.2.0 (126). The results showed that QuizWhizzer obtained a media expert validation score of 91.25% and a material expert validation score of 81.25%, both categorized as highly valid. Student responses reached 88.125%, categorized as highly practical. The N-Gain analysis showed an average score of 0.9583 or 95.83%, which falls into the high category. Therefore, QuizWhizzer is considered highly valid, highly practical, and effective for IPAS learning on currency values and their functions in third-grade elementary school students